Menjadi SDM Unggul di Era Digital Pada BKPRMI Kabupaten Asahan - Santoso Santoso; Elly Rahayu; Wan Mariatul Kifti; Syahira Syahira; Tri Anjar Ningsih (Smart Education, 2022)
Abstract: Community service activities were carried out by the STMIK Royal lecturer team in the form of HR development training with the theme